Dampak Perceraian terhadap Perkembangan Sosial dan Emosional Anak - Rahiel Najmatul Jannah Kuriawan; Rosmiati Rosmiati; Bahrun Bahrun; Sitti Mulya Rizka; Rahmatun Nessa (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Divorce is a phenomenon that has been increasingly observed in Banda Aceh City based on Statistics Indonesia data from 2022–2024. This condition raises serious issues for children, particularly in their social and emotional development. Children from divorced families often experience feelings of loss, emotional instability, and difficulties in forming social relationships. These problems are exacerbated by the limited role of parents in providing guidance and affection after the divorce. This study aims to examine the impact of divorce on children’s social and emotional development. The research employs a qualitative approach using a descriptive research method. The subjects of this study consist of four respondents representing two different cases concerning the impact of divorce on children. Data were collected through semi-structured interviews. Based on the resuts of research conducted in Lampaseh Aceh, Banda Aceh, the findings indicate that divorce has a significant impact on children’s social and emotional development from early childhood through adolescence. Early childhood children are more affected in emotional aspects, such as heightened sensitivity, feelings of guilt, and the loss of a father figure. Adolescents, on the other hand, experience impacts such as identity crises, low self-confidence, negative perceptions of marriage, and a greater tendency to seek support from peers. Family support, consistency in parenting patterns, and the role of schools are important factors in helping children adapt and rebuild a sense of security after divorce